2003
DOI: 10.1073/pnas.2134064100
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 in genital tract and plasma of women: Compartmentalization of viral sequences, coreceptor usage, and glycosylation

Abstract: Worldwide, 90% of HIV-1 infections are transmitted heterosexually. Because the genital mucosa are the sites of initial contact with HIV-1 for most exposed individuals, study of the virus from the genital tract is critical for the development of vaccines and therapeutics. Previous analyses of HIV-1 in various tissues have documented compartmentalization of viral genomes. Whether compartmentalization was associated with viral phenotypic differences or immune status, however, was not well understood. We compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
110
1
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 106 publications
(118 citation statements)
references
References 35 publications
6
110
1
1
Order By: Relevance
“…These data provide strong evidence for the presence of distinct populations of HIV-1 replicating in each site. Although we did not discern sequences that conferred different phenotypes on the viruses in each compartment, such differences have been observed (8,9,24,44,54). The detailed documentation of HIV-1 compartmentalization presented here underscores the potential for distinct, clinically relevant characteristics such as antiretroviral resistance or coreceptor usage in separate, biologically significant compartments.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…These data provide strong evidence for the presence of distinct populations of HIV-1 replicating in each site. Although we did not discern sequences that conferred different phenotypes on the viruses in each compartment, such differences have been observed (8,9,24,44,54). The detailed documentation of HIV-1 compartmentalization presented here underscores the potential for distinct, clinically relevant characteristics such as antiretroviral resistance or coreceptor usage in separate, biologically significant compartments.…”
Section: Discussionmentioning
confidence: 62%
“…pressure in the separate compartments (61). Another study, which examined women with a spectrum of immune states, demonstrated an association of higher CD4 ϩ cell counts and compartmentalization of HIV-1 env sequences, providing evidence that the immune response influences the development of viral genotypes in each compartment (24).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is no obvious single tissue mass (equivalent to the prostate, for example) that could provide a source of localized virus production. Several studies have reported compartmentalization of viral sequences in the FMTwithin at least a subset of subjects (Poss et al 1998;Kemal et al 2003;Adal et al 2005;Andreoletti et al 2007). More recently, this compartmentalization was interpreted to be largely the result of clonal amplification (Bull et al 2009).…”
Section: Genital Tractmentioning
confidence: 99%